2003
DOI: 10.1111/j.0013-8703.2004.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Host tree resistance against the polyphagous wood‐boring beetle Anoplophora glabripennis

Abstract: Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae: Lamiini) is an invasive woodboring beetle with an unusually broad host range and a proven ability to increase its host range as it colonizes new areas and encounters new tree species. The beetle is native to eastern Asia and has become an invasive pest in North America and Europe, stimulating interest in delineating host and non-host tree species more clearly. When offered a choice among four species of living trees in a greenhouse, adult A. gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 20 publications
(26 reference statements)
3
50
1
Order By: Relevance
“…Several tree characteristics are thought to affect the PBM of P. quercivorus, including sapwood hardness (Green et al 2004) and resistant response (Morewood et al 2004). Future research should clarify differences in these characteristics among tree species in relation to their susceptibility to P. quercivorus.…”
Section: Discussionmentioning
confidence: 99%
“…Several tree characteristics are thought to affect the PBM of P. quercivorus, including sapwood hardness (Green et al 2004) and resistant response (Morewood et al 2004). Future research should clarify differences in these characteristics among tree species in relation to their susceptibility to P. quercivorus.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed physical mechanisms of resistance include high rates of sap flow (Morewood et al, 2004) and specialized water-containing vesicles (Hanks et al, 1991(Hanks et al, , 1999, which can inhibit larval establishment. Additionally, induction of wound periderms (callus tissues) in response to larval feeding is hypothesized to function defensively by encapsulating larvae (Anderson, 1944;Dunn et al, 1990;Fierke and Stephen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, induction of wound periderms (callus tissues) in response to larval feeding is hypothesized to function defensively by encapsulating larvae (Anderson, 1944;Dunn et al, 1990;Fierke and Stephen, 2008). Putative chemical mechanisms of resistance include constitutive and induced secondary metabolites present in bark and phloem tissues (Morewood et al, 2004). For example, differences in phenolic profiles in stem phloem tissues of resistant and susceptible ash species were implicated as resistance mechanisms to emerald ash borer (Eyles et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…and Acer negundo L.. It was reported that 18 genera were damaged by Anoplophora glabripennis and great economic loses had been made (Keena, 2002;Smith and Bancroft, 2002;Morewood et al, 2004). The volatiles emitted from the host plant play an important role for insects in finding their targets.…”
Section: Introductionmentioning
confidence: 99%